2007
DOI: 10.3177/jnsv.53.522
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Intake of Vegetables, Fruit, and Grains and the Prevalence of Tooth Loss in Japanese Women

Abstract: Summary Epidemiological evidence regarding dental status and its relationship to diet and nutritional status has been limited. The present cross-sectional study examined the relationship between intake of vegetables, fruit, grains, antioxidants, and fiber and the prevalence of tooth loss. Study subjects were 1,002 pregnant Japanese women. Tooth loss was defined as the previous extraction of 1 or more teeth. Adjustment was made for age, gestation, parity, cigarette smoking, passive smoking at home and at work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
0
13
1
Order By: Relevance
“…A study by Marcenes et al (4) showed a low intake of non-starch polysaccharides, proteins, iron, calcium, niacin and vitamin C in subjects with fewer teeth. A study by Tanaka et al (24) did not reveal any relationship between intake of vegetables, fruits, antioxidants, soluble fibers, vitamin C, vitamin B and beta-carotene on the one hand and the incidence of edentulism in Japanese women on the other hand, in contrast to the results of the present study.…”
Section: Advances In Bioscience and Clinical Medicinecontrasting
confidence: 99%
“…A study by Marcenes et al (4) showed a low intake of non-starch polysaccharides, proteins, iron, calcium, niacin and vitamin C in subjects with fewer teeth. A study by Tanaka et al (24) did not reveal any relationship between intake of vegetables, fruits, antioxidants, soluble fibers, vitamin C, vitamin B and beta-carotene on the one hand and the incidence of edentulism in Japanese women on the other hand, in contrast to the results of the present study.…”
Section: Advances In Bioscience and Clinical Medicinecontrasting
confidence: 99%
“…Demographic and methodological data were extracted for the following confounding factors: stage of gestation, age, ethnicity, socioeconomic status (SES), smoking status, year of sample recruitment, and dietary assessment tool. Three studies reported data from the Osaka Maternal and Child Health Study 30–32 . Data were combined to provide a larger data set of nutrient variables; the data set is referred to as an individual study in analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies reported data from the Osaka Maternal and Child Health Study. [30][31][32] Data were combined to provide a larger data set of nutrient variables; the data set is referred to as an individual study in analyses. Due to the large number of studies included, original authors were contacted only to confirm the year the study sample was recruited.…”
Section: Data Extractionmentioning
confidence: 99%
“…A diet history questionnaire, consisting of 110 food items selected mainly from a food list used in National Nutrition Survey of Japan, was developed for use in health education. Tanaka and colleagues used this diet history questionnaire to hypothesize a negative relationship between tooth loss prevalence and the intake of magnesium [8], and also between tooth loss and the insoluble fiber foods [9] among Japanese women. However, the reliability of this instrument was not reported.…”
Section: Introductionmentioning
confidence: 99%